Drafting - Macdonald, Ros (Roslyn), 1947-; McGill, Denise, 1952- (Chatswood, N.S.W. : LexisNexis Butterworths, 2008)
Contents: General Principles of Drafting; Deeds; Special conditions; Options; Leases; Sale and purchase of a business; Torrens title mortgages; Guarantees; Trusts and trustees.'--Provided by publisher.
1. General principles of drafting -- 2. Deeds -- 3. Special conditions -- 4. Options -- 5. Leases -- 6. Sale and purchase of a business -- 7. Torrens title mortgages -- 8. Guarantees -- 9. Trusts and trustees.
Includes index.
Previous ed.: Butterworths,1997.
Includes bibliographical references and index.
Keywords: Contracts -- Australia; Legal composition